Dynamic pattern of postprandial bile acids in paediatric non‐alcoholic fatty liver disease - Huang, Jiating; Lin, Hu; Liu, A‐Na; Wu, Wei; Alisi, Anna; Loomba, Rohit; Xu, Cuifang; Xiang, Wenqin; Shao, Jie; Dong, Guanping; Zheng, Ming‐Hua; Fu, Junfen; et al. (Liver international, 2024)
Background Dysregulation of bile acids (BAs), as important signalling molecules in regulating lipid and glucose metabolism, contributes to the development of non‐alcoholic fatty liver disease (NAFLD). However, static BA profiles during fasting may obscure certain pathogenetic aspects. In this study, we investigate the dynamic alterations of BAs in response to an oral glucose tolerance test (OGTT) among children with NAFLD. Methods We recruited 230 subjects, including children with overweight/obesity, or complicated with NAFLD, and healthy controls. Serum BAs, 7‐hydroxy‐4‐cholesten‐3‐one (C4) and fibroblast growth factor 19 (FGF19) were quantified during OGTT. Clinical markers related to liver function, lipid metabolism and glucose metabolism were assessed at baseline or during OGTT. Findings Conjugated BAs increased while unconjugated ones decreased after glucose uptake. Most BAs were blunted in response to glucose in NAFLD (p > .05); only glycine and taurine‐conjugated chenodeoxycholic acid (CDCA) and cholic acid (CA) were responsive (p < .05). Primary BAs were significantly increased while secondary BAs were decreased in NAFLD. C4 and FGF19 were significantly increased while their ratio FGF19/C4 ratio was decreased in NAFLD. The dynamic pattern of CDCA and taurine‐conjugated hyocholic acid (THCA) species was closely correlated with glucose (correlation coefficient r = .175 and −.233, p < .05), insulin (r = .327 and −.236, p < .05) and c‐peptide (r = .318 and −.238, p < .05). Among which, CDCA was positively associated with liver fat content in NAFLD (r = .438, p < .05). Additionally, glycochenodeoxycholic acid (GCDCA), CDCA and THCA were potential biomarkers to discriminate paediatric NAFLD from healthy controls and children with obesity. Interpretation This study provides novel insights into the dynamics of BAs during OGTT in paediatric NAFLD. The observed variations in CDCA and HCA species were associated with liver dysfunction, dyslipidaemia and dysglycaemia, highlighting their potential roles as promising diagnostic and therapeutic targets in NAFLD.